2021
DOI: 10.3390/nu13031021
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Associated Inflammation: Does Curcumin Exert a Beneficial Role?

Abstract: Curcumin is a lipophilic polyphenol, isolated from the plant turmeric of Curcuma longa. Curcuma longa has always been used in traditional medicine in Asian countries because it is believed to have numerous health benefits. Nowadays it is widely used as spice component and in emerging nutraceutical food worldwide. Numerous studies have shown that curcumin possesses, among others, potential anti-inflammatory properties. Obesity represents a main risk factor for several chronic diseases, including type 2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…We found that adipocyte viability was not significantly affected by curcuminoids at concentrations ≤ 20 µM, demonstrating that these compounds suppressed adipogenesis through means other than apoptosis induced by membrane lysis. Curcumin is reported to attenuate obesity-related disorders via different mechanisms, such as transcription factors, cellular receptors, growth factors, cytokines, and chemokines [16]. An increase in adipose tissue is generated by the increased size and number of lipid droplets in adipocytes [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that adipocyte viability was not significantly affected by curcuminoids at concentrations ≤ 20 µM, demonstrating that these compounds suppressed adipogenesis through means other than apoptosis induced by membrane lysis. Curcumin is reported to attenuate obesity-related disorders via different mechanisms, such as transcription factors, cellular receptors, growth factors, cytokines, and chemokines [16]. An increase in adipose tissue is generated by the increased size and number of lipid droplets in adipocytes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin can directly interact with a wide range of biomolecules, such as transcription factors, cellular receptors, and enzymes, for attenuating obesity-related disorders via different signaling mechanisms [16,44]. Curcumin is proved to inhibit the mRNA level of adipogenic transcription factors, particularly PPARγ and C/EBPα, in the early stage of adipocyte differentiation [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this paper and its focus on pre-existing CHRi in individuals, it must be noted that there is an intimate connection between obesity and CHRi. Obesity gives rise to inflammation, and inflammation also gives rise to obesity; [133][134][135] the reason being that adipocytes secrete PI cytokines that promote further adipocyte growth, giving rise to a feedback loop that leads to increase in CHRi once obesity sets in, with involvement of the liver, and of the acute phase proteins, in this feedback loop. [136] It seems likely that this is related to nutrition, diet and lifestyle.…”
Section: Connections Between Obesity and Inflammation And Obesity And Covid-19mentioning
confidence: 99%
“…These findings indicate that placental adaption to maternal environmental stimuli can influence fetus programming with long-term effects [ 57 ]. Of note, the plasticity of the placenta allows fetal signals to influence in a sex-specific manner maternal health as well [ 4 ]. However, the complex interaction between placental function and fetal development is not well known.…”
Section: The Importance Of Sexual Dimorphism In Placental Ncrnas Expressionmentioning
confidence: 99%
“…It is well known that fetal growth and development occur in a sexually dimorphic manner [ 3 ]. However, growing evidence indicates that fetal sex differently influences the course of pregnancy and associated complications, as well maternal health [ 4 , 5 , 6 , 7 ]. Although ethnic differences exist in the maternal response, several data indicate that women carrying a male show an increased risk of gestational diabetes (GDM), placental abruption [ 7 , 8 ], and preterm birth [ 9 ], whereas gestational hypertension/preeclampsia (PE) appear to be linked to carrying a female fetus [ 10 ].…”
Section: Introductionmentioning
confidence: 99%